2020
DOI: 10.1038/s41598-020-63118-0
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular Lens Power Calculation after Small Incision Lenticule Extraction

Abstract: With more than 1.5 million Small Incision Lenticule Extraction (SMILE) procedures having already been performed worldwide in an ageing population, intraocular lens (IOL) power calculation in post-SMILE eyes will inevitably become a common challenge for ophthalmologists. Since no refractive outcomes of cataract surgery following SMILE have been published, there is a lack of empirical data for optimizing IOL power calculation. Using the ray tracing as the standard of reference-a purely physical method that obvia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 20 publications
2
20
0
Order By: Relevance
“…They evaluated the predictability of IOL power calculation after SMILE using ray tracing (Oculix based on Pentacam data) and found that ray tracing was the most accurate approach for IOL power calculation after myopic SMILE, with 81.9% and 98% of cases with an absolute PE of 0.5 D and 1 D or less, respectively. Another recent study has used ray tracing calculation as a benchmark in a theoretical study of IOL power calculation after SMILE [12]. These results, as well as those in our study, support the advantages of ray tracing for corneal power measurements and IOL calculation after SMILE.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…They evaluated the predictability of IOL power calculation after SMILE using ray tracing (Oculix based on Pentacam data) and found that ray tracing was the most accurate approach for IOL power calculation after myopic SMILE, with 81.9% and 98% of cases with an absolute PE of 0.5 D and 1 D or less, respectively. Another recent study has used ray tracing calculation as a benchmark in a theoretical study of IOL power calculation after SMILE [12]. These results, as well as those in our study, support the advantages of ray tracing for corneal power measurements and IOL calculation after SMILE.…”
Section: Discussionsupporting
confidence: 89%
“…The same result was obtained using Haigis formula in SMILE eyes by Pan et al [19] and Wei et al [31], using Pentacam to measure corneal power. In two recent theoretical studies, involving virtual implantation of an IOL, Haigis L and Shammas performed worse than Masket formula, ray tracing (Okulix), Barrett True K and Potvin-Hill formula [12,13]. As stated before, Gylkerne et al [10] found that LAISK and SMILE induce distinct changes in the anterior corneal shape, and thus, strategies developed to calculate IOL power calculation after LASIK may not be valid after SMILE.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…One study using ray tracing as the standard of reference analyzed the agreement of various IOL power calculation formulas derived from the American Society of Cataract and Refractive Surgeons (ASCRS) postkeratorefractive surgery online calculator and found that the Masket formula showed the smallest mean prediction error (-0.36 AE 0.32 D) and MedAE (0.33 D), and yielded the largest percentage of eyes within AE0.50 D (70%). Noninferior refractive prediction error and AE0.50 D accuracies were achieved by the Barrett True-K, Barrett True K No History and the Potvin-Hill formula [34]. Use of these formulas in conjunction with ray tracing is recommended until sufficient data for empiric optimization of IOL power calculation after SMILE is available [34].…”
Section: Accuracy Of Intraocular Formulas In Eyes With Previous Corne...mentioning
confidence: 99%